(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we initiate the solvability and stability for a class of singular fractional (p, q)-difference equations. First, we obtain an existence theorem of solution for the fractional (p, q)-difference equation. Then, by using a fractional (p, q)-Gronwall inequality, some stability criteria of solution are established, which also implies the uniqueness of solution.